An Integrated View of Organic Biomarker‐Based Sea Surface Temperature Changes in the Subarctic Pacific Since the Last Ice Age. Issue 12 (20th December 2022) - Li, Qian; Chen, Min‐Te; Li, Guangxue; Yu, Jimin; Zou, Jianjun; Shi, Xuefa; Liu, Shidong; Yu, Pai‐Sen
Abstract: The phase relationships of sea surface temperature (SST) changes between the North Pacific and North Atlantic during deglacial millennial‐scale climate events have been of great interest. However, uncertainties remain partly due to the sparsity of deglacial SST records in the North Pacific. This study presents a new high‐resolution T E X 86 L ${TEX}_{86}^{L}$ ‐SST record spanning the entire last deglaciation from core LV63‐41‐2 retrieved from the Northwestern Pacific off the Kamchatka Peninsula, which allows us to explore regional SST change patterns and associated driving mechanisms by compiling previously published SST data in the subarctic Pacific. The subarctic Pacific SST changes during the Bølling‐Allerød and Younger Dryas show in‐phase relationships in response to the North Atlantic SST variations, suggesting a dominant control of atmospheric teleconnections between both oceans. During Heinrich Stadial 1 (HS1) when the North Atlantic exhibited significant cooling, the subarctic Pacific SST developments are complex, showing gradual warming from the Last Glacial Maximum to HS1 in the Northwestern Pacific and cooling at the onset of HS1 in the Northeastern Pacific. We suggest that the inconsistent phase responses resulted from the combined effects of multiple processes, which involve an enhanced poleward advection of warm subtropical waters, cold meltwater inputs from the retreating Cordilleran Ice Sheet into the Northeastern Pacific, and a persistent La Niña‐like state in the tropical Pacific. Key Points: New insights into subarctic Pacific sea surface temperature (SST) changes and their driving mechanisms since the last ice age Different SST responses between the Northwestern and Northeastern Pacific to the North Atlantic cooling during Heinrich Stadial 1 (HS1) Multiple high‐ and low‐latitude processes resulted in inconsistent phase responses during HS1